International prosecutors - Reydams, Luc.; Wouters, Jan, 1964-; Ryngaert, Cedric (Oxford : Oxford University Press, 2012)
The prosecution plays a crucial part in any international war crimes trial, but its role is rarely analysed. This book will assess the work of the prosecutor in a dozen international criminal courts and tribunals, setting out the applicable rules and analysing his or her independence, accountability, and political impact.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Prosecution (International law)